Efektivitas Teknik Self-Monitoring dan Stimulus Control dalam Mengurangi Perilaku Impulsive Buying pada Mahasiswa melalui E-Commerce - Hapsari, Aghista Dwi; Amiroh, Jihan Anissa Innaya; Jamaluddin, Muhammad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The rapid development of e-commerce technology has given rise to the phenomenon of impulsive buying, especially among students. Emotional impulses, attractive promotional offers and ease of transaction make students prone to making unplanned purchases. The purpose of this study was to know the effectiveness of self-monitoring and stimulus control techniques in reducing impulsive buying behavior in college students. The method used was a single-subject experiment with an ABA design. Interventions are conducted by providing treatment based on strengthening self-control and coping against external stimuli that trigger consumption behaviors. The results of the study showed there was a decrease in the impulsive buying score from 59 (medium category) at the initial baseline phase to 39 (low category) at the final baseline. These results indicate the presence of positive behavior changes following the intervention and support the use of this technique as a simple yet effective strategy to manage students’ consumer behavior.